Implementasi Kompetensi Nazhir Wakaf Dalam Peningkatan Kesejahteraan Umat Di Kota Surakarta 2024 - Mudloaf; Khoiruddin Nasution; A. Dardiri Hasyim (Jurnal Ilmiah Ekonomi Islam, 2025)
This research is intended to capture whether the nazhiran practices that have been carried out by nazhir, whether individual nazhir, institutions or organizations, have carried out their mandate according to the standards of Law No. 41 of 2004 or not?, in helping to improve the welfare of the people. This study is a qualitative research, using grounded theory methods with a sociological and anthropological approaches from the study of normative juridcal theory still prevailing, with nazhirs, BWI administrators, and those related to wakaf being the subject of research, while the object is any things or variables being the focus of research. This study belongs to field research, that is descriptive analysis in presenting its finding, sourced from primary and secondary data collected through interview, observation, documentation and focus group discussion (FGD) as the techniques of collecting data. The technique of analysis used is Miles and Huberman’s theory involving data collecting, data reduction, data display, and conclusion. The results of this research, firstly, the majority of nazhirs, both individuals, organizations and institutions, are not yet competent, secondly, it turns out that BWI Surakarta City as the controller of waqf regulations needs to improve and strengthen internally and externally, BWI should collaborate with parties, both professional organizations and ministries or institutions Keywords: Competency, BWI, and People’s Welfare